Model-Based Engineering of Supervisory Controllers using CIF - Schiffelers, Ramon; Theunissen, Rolf; van Beek, Dirk; Rooda, Jacobus (Electronic Communications of the EASST, 2010)
In the Model-Based Engineering (MBE) paradigm, models are the core elements in the design process of a system from its requirements to the actual implementation of the system. By means of Supervisory Control Theory (SCT), supervisory controllers (supervisors) can be synthesized instead of designing them manually. In this paper, a framework based on the Compositional Interchange Format for hybrid systems (CIF) has been developed that integrates the MBE and the SCT paradigms. To illustrate the framework, an industrial-size case study has been performed: ’synthesis of a supervisory controller for the patient support system of an MRI scanner’. In this case study, we address 1) modelling of the components and the control requirements; 2) synthesis of the supervisor; 3) simulation of the synthesized supervisor and a hybrid model of the plant; and 4) real-time, simulation based control of the supervisor and the actual patient support system of the MRI scanner.